Application Of The “Variable Costing” Method In Short-Term Decision Making To Accept Special Orders Onrainbow Production, Parepare City - Ruslan Ruslan; Abdul Azis; Irin Triastuti (Journal AK-99, 2023)
The price of a product or order can be determined by calculating production costs. This includes all costs incurred to make the product, such as labor, materials, and equipment. Sometimes, only certain costs, such as variable costs, matter to managers. This study is to determine how Pelangi Production can use the variable costing method to accept orders in the short term. The existing semi-variable costs are first divided into fixed and variable costs using the data analysis method. using the least squares method, and second, figuring profit and loss both without orders and with orders that aren't reasonable. The consequences of the review show an examination involving variable costing in pursuing choices to acknowledge or dismiss extraordinary orders at the Pelangi Creation organization from orders from the Edho assortment shop so that screen printing shirts can be acknowledged. because a profit of IDR 37 could be generated by this special order. 345,738 with a total revenue of IDR 308,268,900 and pertinent expenses of IDR 21,533,900. Since the fees incurred are less than the revenue generated, it is recommended that the special order be accepted.